Protein: Importance and quality evaluation - เกรียงสินยศ, วันทนีย์; ประจันสุวรรณ, อารีย์ (Journal of Nutrition Association of Thailand (Online), 2016)
Protein is an essential nutrient for whole body particularly growth and development. Protein requirement for each people is determined by gender, age and health status. Dietary protein can be derived from both plant and animal sources which may have differences in protein quality. High quality protein is very important for support health in early and later life. The protein quality of food depends on the amount of indispensable amino acids and also its digestibility. Some foods are high in amino acids, but their digestibility are limited by the anti-nutritional factors. Hence, it is necessary to study the protein quality for preparing and coping with health, nutritional security and climate change problems. Furthermore, it can be used for creating and developing new recipes to improve food quality.